Biological Treatments in Behçet's Disease: Beyond Anti-TNF Therapy. (30th June 2014) - Caso, Francesco; Costa, Luisa; Rigante, Donato; Lucherini, Orso Maria; Caso, Paolo; Bascherini, Vittoria; Frediani, Bruno; Cimaz, Rolando; Marrani, Edoardo; Nieves-Martín, Laura; Atteno, Mariangela; Raffaele, Carmela G. L.; et al.
Abstract : Behçet's disease (BD) is universally recognized as a multisystemic inflammatory disease of unknown etiology with chronic course and unpredictable exacerbations: its clinical spectrum varies from pure vasculitic manifestations with thrombotic complications to protean inflammatory involvement of multiple organs and tissues. Treatment has been revolutionized by the progressed knowledge in the pathogenetic mechanisms of BD, involving dysfunction and oversecretion of multiple proinflammatory molecules, chiefly tumor necrosis factor- (TNF-) α, interleukin- (IL-) 1 β, and IL-6. However, although biological treatment with anti-TNF- α agents has been largely demonstrated to be effective in BD, not all patients are definite responders, and this beneficial response might drop off over time. Therefore, additional therapies for a subset of refractory patients with BD are inevitably needed. Different agents targeting various cytokines and their receptors or cell surface molecules have been studied: the IL-1 receptor has been targeted by anakinra, the IL-1 by canakinumab and gevokizumab, the IL-6 receptor by tocilizumab, the IL12/23 receptor by ustekinumab, and the B-lymphocyte antigen CD-20 by rituximab. The aim of this review is to summarize all current experiences and the most recent evidence regarding these novel approaches with biological drugs other than TNF- α blockers in BD, providing a valuable addition to the actually available therapeutic armamentarium.